2023
DOI: 10.7554/elife.81743
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic mapping and functional characterization of human New World hantavirus neutralizing antibodies

Abstract: Hantaviruses are high-priority emerging pathogens carried by rodents and transmitted to humans by aerosolized excreta or, in rare cases, person-to-person contact. While infections in humans are relatively rare, mortality rates range from 1 to 40% depending on the hantavirus species. There are currently no FDA-approved vaccines or therapeutics for hantaviruses, and the only treatment for infection is supportive care for respiratory or kidney failure. Additionally, the human humoral immune response to hantavirus… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
16
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 16 publications
(16 citation statements)
references
References 79 publications
0
16
0
Order By: Relevance
“…Our literature search identified 24 amino acid changes in the Gc that convey neutralization escape from antibodies against PUUV, Hantaan virus (HTNV), Andes virus (ANDV), and Sin Nombre virus (SNV) (Table S1, available in the online version of this article). We note that 21 of the 24 sites were reported in 2020 or later [15–17], allowing us to perform the most comprehensive mapping of Gc neutralization escape mutation sites to date.…”
Section: Full-textmentioning
confidence: 99%
See 4 more Smart Citations
“…Our literature search identified 24 amino acid changes in the Gc that convey neutralization escape from antibodies against PUUV, Hantaan virus (HTNV), Andes virus (ANDV), and Sin Nombre virus (SNV) (Table S1, available in the online version of this article). We note that 21 of the 24 sites were reported in 2020 or later [15–17], allowing us to perform the most comprehensive mapping of Gc neutralization escape mutation sites to date.…”
Section: Full-textmentioning
confidence: 99%
“…Beyond the insights gained from the spatial distribution of NE sites, we note that specific regions within the Gc may be under strict functional constraints that could limit the occurrence of NE mutations, despite the importance of these regions for antibody-mediated neutralization. Recent evidence has shown that the apex of Gc domain II, containing the hantaviral fusion loops, and targeted by ADI-42898 () [14], ADI-37236 and ADI-42089 [16], and SNV-53 [15], presents such a site. Taken together, the picture emerging from recent structural and functional findings highlights at least two prominent regions of vulnerability in hantaviral Gc: the region of the 4G2 epitope that lies at the junction of domains I and II (possibly extending to the top of domain I), and the tip of Gc domain II that houses the fusion loops, shielded by Gn.…”
Section: Full-textmentioning
confidence: 99%
See 3 more Smart Citations